ANALISIS KOMPONEN KIMIA EKSTRAK METANOL FRAKSI PETROLEUM ETER DAUN EUPATORIUM ODORATUM DENGAN GC-MS - Purwati Purwati; Sabirin Matsjeh (Molekul, 2008)
The purpose of this investigation was to analize the organic compounds of Eupatorium odoratum leaf and identification of the compounds using Gas Chromatography Mass Spectrometry (GC-MS). The sample was soaked in metanol. The extract of metanol was partitioned using petroleum ether. The extracts obtained were analyzed and identified by GC-MS. The results showed that in the extract of petroleum ether contained the organic compounds: germacrene, isocaryophyllene, 2,6,6,9-tetramethyl-1,4,8-cycloundecatriene, 1-methyl-5-methylene-8-(1-methylethyl)-1,7-cyclodecadiene, 1,2,4a,5,8,8a-hexahydro-4,7-dimethyl-1-(1-methylethyl) naphthalene, 1,12- dodecanediol, octahydro-1-(2-octyldecyl) pentalene, 3,7,11,15-tetramethyl-2-hexadecen-1-ol, methyl (12-acetyloxy)-9-octadecanoic, bis (2-ethylhexyl) phthalat, farnesol, 4,22-cholestadien-3-one and 1,2,3,5,6,7,8,8a-octahydro-1,4-dimethyl-7-(1-methylethenyl) azulene. In the extract of ethyl acetate contained the organic compounds: methyl heptadecanoic, hexadecanoic acid, methyl 13-octadecenoic, 14,16-octadecadienal and octadecanoic acid.